Mobile phones like any other ICT? The case of Greece and its adoption of mobile phones from a socio-cultural perspective - Panayiota Tsatsou (Adoption, Usage, and Global Impact of Broadband Technologies: Diffusion, Practice and Policy, 2011)
This chapter explores mobile phones and how they have been received in juxtaposition with the Internet and in close association with socio-cultural contexts of life. By examining the Greek case and its particularities, the chapter provides some sense of why different Information and Communication Technologies (ICTs), such as mobile phones and the Internet, might be received and adopted differently by people living in the same socio-cultural context (at the national level). In the case of Greece, statistical and historical data confirm the contrasting receptions of mobile phones and the Internet but empirical evidence is lacking to explain the exceptionally high adoption rates of mobile phones in the country. Thus, the chapter reports on original empirical evidence obtained in elite actors’ interviews and focus groups of ordinary people to explain the contrasting ways mobile phones and the Internet have been received in the country. On the basis of these empirical findings, the chapter finds that certain socio-cultural contexts, such as that of Greece, favour mobile phones more than the Internet, thus making mobile telephony a distinctive case of ICT.